Pengembangan Pembelajaran Kimia Larutan Berdasarkan Ilmu Pengetahuan dan Pengaruhnya Terhadap Hasil Belajar dan Minat Siswa di Kelas XI SMA - Ramlan Silaban; Freddy Tua Musa Panggabean; Sary Marcella Sitompul; Patricia Rohana Septiana Simarmata; Irving Yosafat Silaban (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2019)
This study aims to obtain chemistry-based teaching materials for scientific literacy on buffer solution materials that meet BSNP criteria, and to the extent able to improve the chemistry learning outcomes of high school students. This type of research is the development of ADDIE research model carried out in class XI MIA SMA Parulian 1 Medan. The instruments used were test and non-test instruments that had fulfilled validity. The study was conducted in 2 stages, namely the manufacturing phase of teaching materials based on scientific literacy and the limited trial phase. The results of the study are (1), it has been obtained teaching materials Buffer Solution based on science literacy that meet BSNP standards namely content eligibility = 3.51, presentation eligibility = 3.49, Language eligibility = 3.64, and feasibility of graphic = 3.69. (2), the results of limited trials in learning indicate that the average value of student learning outcomes in experimental class I was 83.10 higher than experimental class II of 75.24. (3), the results of limited trials in learning showed that the average student interest in the experimental class I was 79.33 higher than in the experimental class II which was 69.45.